Mendeley co-readership 정보를 활용한 한국 관련 논문의 글로벌 독자 국가 네트워크 분석 - 조재인; 박종도; Cho, Jane; Park, Jong-Do (Chŏngbo Kwalli Hakhoechi, 2018)
Mendeley readership data could be used to understand how research outcome be spent outside of academia in multi way. So it could be utilized to understand unknown world which citation rate could not explain still now. This study, by conducting a country network analysis using Mendeley's co readership data about articles of Korea related research, clusters countries that share common academic interest. As a result, the US and other advanced countries in all fields showed high overall and regional centrality, indicating that they have overall cooperation and potential for exchange of Korea related studies. Some developing countries have shown high regional centrality and are linked to common academic interests. In the medical and social sciences, the OECD and developing countries have formed a separate group of readers, and the engineering sector has been characterized by emerging developing countries as a large community of readers. In addition, engineering science field has shown that network density is relatively high, so there might be high possibility of academic exchanges, knowledge dissemination and cooperation among countries. Mendeley의 독자 정보는 학계 밖에서 학문의 결과물이 어떻게 소비되고 있는지 다각도로 파악하여 피인용도로는 해석할 수 없었던 미지의 세계를 예측하는데 활용될 수 있다. 본 연구는 Mendeley의 co-readership 데이터를 활용해 한국 관련 논문의 독자 국가 네트워크 분석을 수행하여 공통의 학문적 관심사를 공유하는 국가 군집을 이해하고 이들 국가가 네트워크 상에서 어떠한 영향력을 가지는지 확인하였다. 그 결과 전 분야에서 미국을 비롯한 선진국은 대체로 높은 전역중심성을 보여 한국 관련 연구에 대한 전반적인 협력과 잠재적 교류 가능성을 가지는 것으로 나타났으며, 일부 개발도상국은 높은 지역중심성을 보여 상호간 공통의 학문적 관심사로 연계되어 있는 것으로 확인되었다. 한편 의학과 사회과학 분야는 OECD 국가와 개발도상국이 분리된 독자층을 이루었으며, 공학 분야는 신흥경제개발국이 대규모 독자 군집으로 형성되는 특징을 보였다. 또한 공학은 네트워크 밀도가 상대적으로 높게 나타나 국가간 학문적 교류와 지식의 확산, 협력의 가능성이 높은 것으로 분석되었다.